2015
DOI: 10.1039/c5ra13005k
|View full text |Cite
|
Sign up to set email alerts
|

Improved electrochemical properties of LiMn2O4 with the Bi and La co-doping for lithium-ion batteries

Abstract: A series of LiBi x La x Mn 2-2x O 4 (x=0, 0.002, 0.005, 0.010, 0.020) samples were synthesized by solution combustion synthesis in combination with calcination. The phase structure and morphology of the products were characterized by X-ray diffraction, scanning electron microscopy, and transition electron microscopy. The results demonstrated that a single-phase LiMn 2 O 4 spinel structure was obtained for the LiBi x La x Mn 2-2x O 4 (x=0, 0.002, 0.005) samples, whereas impurities were observed for the LiBi x L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…LiMn2O4 powders were prepared by solution combustion synthesis (SCS) in combination with calcination [17,29,30]. Lithium nitrate (LiNO3, 99.0%, Kishida Chemical Co., Ltd., Japan), lithium acetate (CH3COOLi, 99.0%, Kishida Chemical Co., Ltd., Japan), manganese nitrate (Mn(NO3)2, 50% w/w aqueous solution, Alfa Aesar), and urea (NH2CONH2, 99.0%, Chameleon Reagent, Japan) were used as the raw materials without further purification.…”
Section: Preparation and Characterization Of Mn 4+ -Rich Phase-modified Limn2o4mentioning
confidence: 99%
See 1 more Smart Citation
“…LiMn2O4 powders were prepared by solution combustion synthesis (SCS) in combination with calcination [17,29,30]. Lithium nitrate (LiNO3, 99.0%, Kishida Chemical Co., Ltd., Japan), lithium acetate (CH3COOLi, 99.0%, Kishida Chemical Co., Ltd., Japan), manganese nitrate (Mn(NO3)2, 50% w/w aqueous solution, Alfa Aesar), and urea (NH2CONH2, 99.0%, Chameleon Reagent, Japan) were used as the raw materials without further purification.…”
Section: Preparation and Characterization Of Mn 4+ -Rich Phase-modified Limn2o4mentioning
confidence: 99%
“…Single-doping of Ni 2+ [9], Al 3+ [10], Cr 3+ [11], Sm 3+ [12], Ru 4+ [13] has been reported. Co-doping with Ni-Cu [14], Cr-Fe [15], Mg-Si [16], and La-Bi [17] has also been carried out. The results have shown that these doped LiMn2O4 spinel materials display enhanced stabilization of their structure and improved cycling performance compared with nondoped LiMn2O4 materials.…”
Section: Introductionmentioning
confidence: 99%
“…and La-Bi [14], has been carried out to retard capacity fading, the irreversible capacity loss arising from the dissolution of manganese cannot be completely alleviated both at room and elevated temperatures [15]. Surface modification, being another effective approach, is drawing more interest, since it can give rise to improved electrochemical properties due to its protective effect at the cathode/electrolyte interfaces, not only suppressing the dissolution of manganese, but also improving operation safety and structural stability [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] So far, many substitutions (S, F, Br, Si, B, Mg, Al, Bi, Cu, Ni, Ru, Ga, Ag, etc. [12][13][14][15][16][17][18][19][20][21][22][23][24] ) have been studied to increase the cycle life of LiMn 2 O 4 cathode. The main idea behind this approach is to suppress the Jahn-Teller distortion via increasing the valance state of Mn ions and to stabilize the spinel structure during cycling.…”
Section: Introductionmentioning
confidence: 99%
“…These studies can be classied in two categories; Lithium Boron Oxide (LBO) coated on the LiMn 2 O 4 and direct doping of B in Mn sites of LiMn 2 O 4 . [12][13][14][15][16][17][18][19][20][21][22][23][24][25]45 48 In this work, we examined the effects of B doping on the structural, magnetic and electrochemical properties of LiMn 2 O 4 . We found that the cell parameters and the cell volume increases with increasing B content.…”
Section: Introductionmentioning
confidence: 99%